Mere Discipleship : Radical Christianity in a Rebellious World - Camp, Lee C. (Grand Rapids : Brazos Press, 2003)
In Mere Discipleship, Lee Camp sets forth his vision of what it means to truly follow Christ, challenging Christians to put obedience to Jesus as Lord ahead of allegiances to all earthly authorities-be they nationalistic, political, economic, or cultural. Camp lays out a sound biblical framework of what disciples believe and therefore what they should do.
pt. 1. Reenvisioning discipleship. "Radical" discipleship ; God's way of working ; Pledging allegiance to the Kingdom of God -- pt. 2. What disciples believe. The Gospel : repent, for the kingdom is at hand ; The Savior : the slaughtered Lamb ; The church : the body of Christ -- pt. 3. What disciples do. Worship : why disciples love their enemies ; Baptism : why disciples don't make good Americans (or Germans, or Frenchmen) ; Prayer : why disciples trust God rather than their own calculations ; Communion : why disciples share their wealth ; Evangelism : how disciples "make a difference."
Includes bibliographical references (pages 195-208).
Keywords: Free churches; Dissenters, Religious; Discipleship and Church - Biblical Teachings